Effects of Coal Dust Exposure in Eosinophil and Interleukin (IL)-13 on Pulmonary Remodeling in Asthmatic Mice Models - Fujiati, Fujiati; Haryati, Haryati (Faculty of Medicine, Universitas Diponegoro, 2024)
Background: Coal dust is an environmental factor contributing to the risk of respiratory diseases. However, clinical evidence on the effects of coal dust in lung remodelling is currently lacking, especially the effect of eosinophils and IL-13. This study investigates how eosinophil and IL-13 affect pulmonary remodeling in coal dust and asthma combination models.Methods: An experimental study was conducted using BALB/c mice aged 6 to 12 weeks with a weight range of 20-25 g. There were 10 mice in each of the three treatments. Groups were sensitized with normal saline, ovalbumin (OVA)-sensitized, and OVA-sensitized + coal dust. The parameters of lung remodeling (the thickness of epithelium, smooth muscle thickness, the number of goblet cells, and subepithelial fibrosis) and the number of eosinophils were measured with histomorphometry analysis. Total IL-13 concentrations were measured using an IL-13 ELISA kit. The data group of a combination of OVA + coal dust was analyzed using the path analysis method.Results: From path analysis, it was found that Eosinophils (b=0.006; 95%CI=-2.594 to 2.606; p=0.000) had positive, direct, and statistically significant effects on IL-13. Eosinophil's indirect effect on epithelium thickness and subepithelial fibrosis thickness via IL-13. Interleukine-13 had positive, direct, and statistically significant effects on epithelium thickness (b=0.67; 95%CI=-0.129 to 1.471; p=0.010) and subepithelial fibrosis thickness (b=0.682; 95%CI=0.301 to 1.062; p=0.000).Conclusion: Eosinophils' indirect effect on lung remodeling via IL-13 and IL-13 directly affects airway remodeling, especially epithelium and subepithelial fibrosis components.